Degradation of OLED performance by exposure to UV irradiation. Issue 72 (23rd December 2019) - Kwon, Sun-Kap; Baek, Ji-Ho; Choi, Hyun-Chul; Kim, Seong Keun; Lampande, Raju; Pode, Ramchandra; Kwon, Jang Hyuk
Abstract : This paper reports the influence of UV radiation on the interface of a co-deposited EIL and Ag : Mg (10 : 1) cathode unit and pixel shrinkage. Abstract : Organic light-emitting diode (OLED) displays are highly susceptible to the harsh environmental conditions found outdoors, like exposure to direct sunlight as well as UV radiation and storage temperature, resulting in a loss of luminance and lifespan, pixel shrinkage, and permanent damage and/or malfunction of the panel. Here, we fabricated top emission OLEDs (TEOLEDs) using Yb : LiF (1 : 1, 2 nm)/Ag : Mg (10 : 1, 16 nm) and Mg : LiF (1 : 1, 2 nm)/Ag : Mg (10 : 1, 16 nm) cathode units and the performances of the devices were investigated by subjecting them to UV radiation. A fabricated red TEOLED (control device), employing a standard Mg : LiF (1 : 1, 2 nm) electron injection layer (EIL) and an Ag : Mg (16 nm) cathode, showed a rapid decrease in luminance and a fast increase in driving voltage at 10 mA cm −2 over time after UV irradiation for 300 h. However, a cathode unit comprising a Yb : LiF (1 : 1, 2 nm) EIL and an Ag : Mg (10 : 1, 16 nm) cathode showed no loss of luminance or increase in driving voltage at 10 mA cm −2 over time after UV irradiation for 300 h. Therefore, we investigated the changes occurring in both cathode units due to UV irradiation using the lift-out FIB-TEM technique and EDS mapping. With UV irradiation for 300 h, Ag atoms migrated toward the center of the cathode, Mg atoms migrated toward the CPL, and no Mg atoms were observed in the EIL area. In contrast, we observed (i) no substantial migration of Ag atoms and they were located at the center of the cathode, (ii) no migration of Mg atoms toward the CPL layer, and (iii) no movement of Yb atoms after UV irradiation. Furthermore, the UV irradiated red TEOLED with an Mg : LiF (1 : 1, 2 nm) EIL showed (i) deterioration in electron injection into the emissive layer (EML) and an increase in the EIL/metal interface resistance, and (ii) a remarkable shift of the J – V curve to the higher voltage side, while almost no such changes were observed in the TEOLD with a Yb : LiF (1 : 1, 2 nm) EIL. Also, an almost identical RGB pixel emitting area was noticed in the Yb : LiF (1 : 1, 2 nm) based devices after UV irradiation for 300 h. These results suggest that Yb could become a good candidate for the cathode unit, providing better device stability against harsh environmental conditions as well as excellent electron injection properties.